Russian Attempts on Constitutional Issue of Insurgent Serbia (1804-1813) - Šarkić, Srđan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
Alongside the struggle for independence, the First Serbian Uprising signified the beginning of the formation of the Serbian state and an overthrow of the feudal order. This fact was already remarked by Leopold von Ranke in his book Die serbische Revolution. The key issue was, of course, the organization of power. The leader of the uprising, Karađorđe Petrović, held the title of „Vožd,“ i.e. leader or chief, which endowed him with sweeping powers. In order to limit them, the most prominent military commanders proposed to establish a Praviteljstvujušči sovjet, i. e. council or government. Karađorđe approved on this at an assembly in the village of Borak on August 15, 1805. But owing to the fact that the relations between the „Vožd“ and the council had not been regulated by a legal document, some mutual conflicts arose. Therefore, several attempst to find a solution to the basic constitutional issue were made.The Russians, trying hereby to ensure their influence in Serbia, made the first of these attempts. The result was a convention between a Russian colonel, Marquis Paulucci (an Italian who first served in the French army before moving to the Russian service in 1806), and Serbian representatives headed by Karađorđe, who gathered in the city of Negotin in Eastern Serbia on June 28, 1807. First of all, the convention expressed the desire of the Serbian people to be under the protection of Russian Tsar and to obtain from him as soon as possible a capable zemljeupravitelj (land governer). Thereupon, this governor was supposed to establish order and, in the name of the Tsar, to give a Konstitucija, a constitution, to the people. Furtheremore, according to the convention, the appointing of Serbian officers was to be carried out in the name of the Russian Tsar and Russian military garrisons were to be stationed in Serbian towns. Karađorđe agreed to the convention, thereby hoping to ensure Russian aid for Serbia, but at the precise moment when the document was to be sealed by him, he excused himself for having lost the seal.
Keywords: agreement; Russian Tsar; the so-called „Paulucci Convention“; Council; Karađorđe; the first Serbian uprising